ICC’s Involvement in Darfur Conflict: Possibility and Prospect - Yordan Gunawan; Ayu Mega Rakhmawati; Salma Rahmi Pratiwi; Ayu Nopiyaranie; Fatimah Nuraini (Varia Justicia, 2021)
The fall of President Al-Bashir in 2019 was a turning point in the Darfur conflict that happened for more than 17 years in Sudan. The conflict has forced 2.5 million people away from homes and killed at least 500,000 people. The humanitarian conflict and crisis are motivated by the inter-ethnic conflict in Sudan. With orders from the U.N. Security Council, on March 4, 2009, at The Hague, the International Criminal Court (ICC) issued an arrest warrant for President of Sudan, Omar Hassan Al-Bashir, on charges of war crimes and crimes against humanity in Darfur. The purposes of the study are to understand the factors behind the Darfur conflict, to understand how effective the Sudanese national judicial system is, and the jurisdiction of ICC in resolving Darfur conflict. The study is normative legal research through literature review with the existing books and journals. Two approaches of normative legal research were used, namely statutory approach and case approach. The result shows that Sudan National Court is ineffective in resolving the conflict and has no willingness to settle the conflict. Furthermore, ICC has jurisdiction to settle the Darfur conflict by order of United Nation Security.